IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA HARAPAN (PKH) TERHADAP PENANGGULANGAN KEMISKINAN PADA MASYARAKAT KECAMATAN CISURUPAN KAB, GARUT - Elba Noorbayinah, - (2022)
This research is motivated by the phenomenon of poverty, one of the problems that is always experienced by developing countries, including Indonesia. In 2007 the government has rolled out a conditional cash transfer program known as the Family Hope Program (PKH) in which the program targets two things, namely providing direct cash assistance, and providing assistance in empowering the poor. This family of hope program is an aid to health and education services, as we know education is a process of influencing students to be able to adapt to the environment which can cause changes both within themselves and in the community. However, the lack of an economy keeps children from going to school and even dropping out of school because they help their families meet the necessities of life. This study aims to determine the implementation of community policies and civic responsibility in carrying out their responsibilities as beneficiaries of the family hope program assistance in Cisurupan District, Garut Regency. This study uses a qualitative approach with a descriptive method which was carried out in Cisurupan District, Garut Regency with the sources of the Social Service, UPPKH as a companion and the people of Cisurupan District who were the beneficiaries of the assistance. This research data collection through observation, interviews and documentation with triangulation techniques. Data were analyzed through data reduction, data presentation and conclusions. The findings in this study are: 1) The process of designing, implementing and evaluating the Family Hope Program (PKH) in an effort to reduce community poverty in Cisurupan District has been carried out properly in accordance with applicable regulations. 2) The effectiveness of the Family Hope Program (PKH) on poverty reduction in the Cisurupan District has been quite effective in helping the community. 3) The efforts made to support the success of the Family Hope Program on the development of civic responsibility in Cisurupan District are by emphasizing the obligations as KPM during socialization.